An Organoruthenium Anticancer Agent Shows Unexpected Target Selectivity For Plectin. Issue 28 (26th May 2017) - Meier, Samuel M.; Kreutz, Dominique; Winter, Lilli; Klose, Matthias H. M.; Cseh, Klaudia; Weiss, Tamara; Bileck, Andrea; Alte, Beatrix; Mader, Johanna C.; Jana, Samir; Chatterjee, Annesha; Bhattacharyya, Arindam; et al.
Abstract: Organometallic metal(arene) anticancer agents require ligand exchange for their anticancer activity and this is generally believed to confer low selectivity for potential cellular targets. However, using an integrated proteomics‐based target‐response profiling approach as a potent hypothesis‐generating procedure, we found an unexpected target selectivity of a ruthenium(arene) pyridinecarbothioamide (plecstatin) for plectin, a scaffold protein and cytolinker, which was validated in a plectin knock‐out model in vitro. Plectin targeting shows potential as a strategy to inhibit tumor invasiveness as shown in cultured tumor spheroids while oral administration of plecstatin‐1 to mice reduces tumor growth more efficiently in the invasive B16 melanoma than in the CT26 colon tumor model. Abstract : Right on target : An unexpected target selectivity of a ruthenium(arene) anticancer agent was found for the scaffold protein plectin by an integrated target‐response profiling. This approach enabled the identification of potential targets of metallodrugs with a labile metal–halido bond in a cellular setting. Plectin targeting shows potential as a strategy to inhibit tumor invasiveness and was validated. The metallodrug is orally active in vivo.